Citizen-general : Jacob Dolson Cox and the Civil War era - Schmiel, Gene (War and society in North America (Athens, Ohio), 2014)
The wrenching events of the Civil War transformed not only the United States but also the men unexpectedly called on to lead their fellow citizens in this first modern example of total war. Jacob Dolson Cox, a former divinity student with no formal military training, was among those who rose to the challenge. In a conflict in which "political generals" often proved less than competent, Cox, the consummate citizen general, emerged as one of the best commanders in the Union army. During his school days at Oberlin College, no one could have predicted that the intellectual, reserved, and book.